2022
DOI: 10.3390/ijerph191710762
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Deep Coal Miners’ Unsafe Behavior Based on HFACS-CM-SEM-SD

Abstract: The unsafe behavior of miners seriously affects the safety of deep mining. A comprehensive evaluation of miners’ unsafe behavior in deep coal mines can prevent coal mine accidents. This study combines HFACS-CM, SEM, and SD models to evaluate miners’ unsafe behaviors in deep coal mining. First, the HFACS-CM model identifies the risk factors affecting miners’ unsafe behavior in deep coal mines. Second, SEM was used to analyze the interaction between risk factors and miners’ unsafe behavior. Finally, the SD model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…On the other hand, the precondition for unsafe behavior exhibits the lowest central value in terms of accident handling, indicating a relatively weaker influence. This is attributed to the fact that if the workplace adopts highly efficient technological and engineering control measures to mitigate the risk of gas leakage or explosions, the impact of employees' unsafe behavior may be comparatively reduced (Yang, Wang, Zhu, Sun, et al, 2022). These measures may encompass intelligent systems, gas detection equipment, risk assessments, and isolation measures, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the precondition for unsafe behavior exhibits the lowest central value in terms of accident handling, indicating a relatively weaker influence. This is attributed to the fact that if the workplace adopts highly efficient technological and engineering control measures to mitigate the risk of gas leakage or explosions, the impact of employees' unsafe behavior may be comparatively reduced (Yang, Wang, Zhu, Sun, et al, 2022). These measures may encompass intelligent systems, gas detection equipment, risk assessments, and isolation measures, among others.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the HFACS model has gradually found its way into the analysis of coal mine accidents. Yang, Wang, Zhu, Sun, et al (2022), drawing inspiration from the tenets of grounded theory, encoded the collected data and employed the HFACS model to comprehensively identify the perilous factors affecting the unsafe behaviors of coal miners. Zhao et al (2014), focusing on the most prevalent gas accidents, consulted the HFACS framework and analyzed the underlying reasons for 100 typical coal mine gas accidents in the past decade using SPSS 13.0.…”
mentioning
confidence: 99%
“…Tian et al [ 17 ] made a quantitative analysis of unsafe behaviors of miners based on the grey theory, and concluded that unsafe behaviors violating labor discipline have the highest risk value, which is an important direction to improve the safety production of coal mines. In addition, Yang et al [ 18 ] analyzed the unsafe behaviors of deep mining miners through the comprehensive use of HFACS-CM, SD, SEM mathematical methods, and found that the physiological state, psychological state, business ability, resource management, and organizational climate are the five major factors affecting the unsafe behaviors of miners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To some extent, it provides technical and theoretical support for describing human behavior characteristics (Qiao et al, 2018;Cao et al, 2019;You et al, 2019;Chen et al, 2022). Based on the existing research results in psychology and physiology, the combination of the generation and action mechanism of human emotions, related scholars have constructed a human behavior model, creating a new direction of human behavior simulation research (Reynolds, 1987;Yang et al, 2022b). At the same time (Reynolds, 1987;Tu and Terzopoulos, 1994;Zhang et al, 2017), used the law of individuals imitating each other in group psychology simulates human behavior (Musse and Thalmann, 1997;Thalmann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%